2021
DOI: 10.1080/19336950.2021.1923199
|View full text |Cite
|
Sign up to set email alerts
|

The anchor domain is critical for Piezo1 channel mechanosensitivity

Abstract: The mechanosensitive channel Piezo1 is a crucial membrane mechanosensor ubiquitously expressed in mammalian cell types. Critical to its function in mechanosensory transduction is its ability to change conformation in response to applied mechanical force. Here, we interrogate the role of the anchor domain in the mechanically induced gating of human Piezo1 channels. Using the insertion of glycine residues at each corner of the triangular-shaped anchor domain to decouple this domain we provide evidence that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous work points towards defective trafficking of G2029 R (Lukacs et al, 2015) but that S217L had normal membrane localization (Faucherre et al, 2020). We showed that both S217L and G2029R displayed reduced N-glycosylation (Li et al, 2020) [in addition to other trafficking defective mutants generated during structure-function studies (Vero Li et al, 2021)] similar to trafficking defective disease causing variants in ion channels such as K v11.1 , which causes long QT syndrome type 2 (Vandenberg et al, 2012). Herein we provided further insight into the molecular mechanisms by which these mutations influence Piezo1 function.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous work points towards defective trafficking of G2029 R (Lukacs et al, 2015) but that S217L had normal membrane localization (Faucherre et al, 2020). We showed that both S217L and G2029R displayed reduced N-glycosylation (Li et al, 2020) [in addition to other trafficking defective mutants generated during structure-function studies (Vero Li et al, 2021)] similar to trafficking defective disease causing variants in ion channels such as K v11.1 , which causes long QT syndrome type 2 (Vandenberg et al, 2012). Herein we provided further insight into the molecular mechanisms by which these mutations influence Piezo1 function.…”
Section: Discussionmentioning
confidence: 74%
“…The cycloheximide chase procedure has permitted visualization of the degradation kinetics of the steady state population of a variety of cellular proteins (Kao et al, 2015). To understand the turnover rate of Piezo1 channels, we applied cycloheximide (CHX) to the culture media of Piezo1 −/− HEK293T cells expressing wild-type (WT) or mutant Piezo1 (S217L and G2029R) fused to GFP (Cox et al, 2016;Li et al, 2020;Vero Li et al, 2021;Ridone et al, 2020;Buyan et al, 2020).…”
Section: S217l and G2029r Piezo1 Are Less Stable Compared To Wild-type Piezo1mentioning
confidence: 99%
See 1 more Smart Citation
“…Probing N-glycosylation status in this manner provides a rapid and reliable method to determine if human Piezo1 variants, that are generated for structure-function studies 33 or in studies of disease-linked variants, exhibit aberrant trafficking exemplified by our data on G2029R, a known trafficking defective Piezo1 variant 28 . We also used glycosylation status to attempt to rescue G2029R using two widely used strategies; low temperature treatment and a pharmacological chaperone 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, the presence of the larger N-glycosylated species of Piezo1 was seen to be a surrogate for the mature membrane protein as it was absent in trafficking-defective mutants. These findings will be useful when assessing the effects of mutations generated during structure-function studies 33 , or when exploring disease-linked PIEZO1 variants. As a proof of concept, we showed that loss-of-function Piezo1 variants such as G2029R that are known to be trafficking-defective 28 lack a larger N-glycosylated species when expressed in vitro.…”
Section: Introductionmentioning
confidence: 99%